Uterine estrogen receptor alpha and progesterone receptor during the follicular and luteal phase in llamas - Bianchi, Carolina Paula (2007)
Estrogen receptor- (ER) and progesterone receptor (PR) were characterized in different endometrial cell types as luminal and glandular epithelium and stroma during the follicular (FP) and the luteal phase (LP) in llamas. Animals were examined daily by transrectal ultrasonography for the determination of the presence of an ovulatory follicle and ovulation was immediately induced by a GnRH injection (Day 0). Endometrial samples were obtained by transcervical biopsies from the left uterine horn on Day 0 (FP) and 9 days after the GnRH injection (Day 9, LP). Blood samples were collected on these days for estradiol 17 and progesterone determination by RIA. An immunohistochemical technique was used to visualize ER and PR immunostaining which was then analyzed by two independent observers. Total positive area and average staining for ER were affected by the phase of the ovarian activity: in the three cell types there was more positive area and intense staining during the FP than during the LP. Similar findings were observed for PR, more positive stained areas were found during the FP than during the LP in the epithelia. In addition, the three cell types had more intense staining during the FP than during the LP. An effect of the cell type for ER and PR was observed; epithelia (luminal and glandular) had more positive stained areas and greater intensity than stromal cells. In conclusion, the results of the present study suggest that in llamas, like in other ruminants, estradiol has a stimulatory effect while progesterone downregulates the ERand PR and that the receptor is cell type specific.